Comparison of the New Adult Ventilator-Associated Event Criteria to the Centers for Disease Control and Prevention Pediatric Ventilator-Associated Pneumonia Definition (PNU2) in a Population of Pediatric Traumatic Brain Injury Patients*. Issue 2 (February 2016) - Cirulis, Meghan M.; Hamele, Mitchell T.; Stockmann, Chris R.; Bennett, Tellen D.; Bratton, Susan L.
Abstract : Objectives: The new Centers for Disease Control and Prevention paradigm for ventilator-associated events is intended to simplify surveillance of infectious and noninfectious complications of mechanical ventilation in adults. We assessed the ventilator-associated events algorithm in pediatric patients. Design: A retrospective observational cohort study. Setting: This single-center study took place in a PICU at an urban academic medical facility. Patients: Pediatric (ages 0–18 yr old) trauma patients with moderate-to-severe traumatic brain injury ventilated for greater than or equal to 2 days. Measurements and Main Results: We assessed for pediatric ventilator-associated pneumonia (as defined by current Centers for Disease Control and Prevention PNU2 guidelines), adult ventilator-associated events, and an experimental ventilator-associated events definition modified for pediatric patients. We compared ventilator-associated events to ventilator-associated pneumonia to calculate the test characteristics. Thirty-nine of 119 patients (33%) developed ventilator-associated pneumonia. Sensitivity of the adult ventilator-associated condition definition was 23% (95% CI, 11–39%), which increased to 56% (95% CI, 40–72%) using the modified pediatric ventilator-associated pneumonia criterion. Specificity reached 100% for both original and modified pediatric probable ventilator-associated pneumonia using ventilator-associated events criteria. Children who developed ventilator-associated pneumonia or ventilator-associated condition had similar baseline characteristics: age, mechanism of injury, injury severity scores, and use of an intracranial pressure monitor. Diagnosis of ventilator-associated pneumonia and ventilator-associated condition portended similarly unfavorable outcomes: longer median duration of ventilation, ICU and hospital length of stay, and more discharges to rehabilitation, home health, or nursing care compared with patients with no pulmonary complication. Conclusions: Both current and modified ventilator-associated events criteria have poor sensitivity but good specificity in identifying pediatric ventilator-associated pneumonia. Despite poor sensitivity, the high specificity of the ventilator-associated events diagnoses does provide a useful and objective metric for interinstitution ICU comparison. Ventilator-associated pneumonia and ventilator-associated condition were both associated with excess morbidity in pediatric traumatic brain injury patients.